2006
DOI: 10.1016/j.jacc.2006.05.016
|View full text |Cite
|
Sign up to set email alerts
|

Rising Rates of Cardiac Rhythm Management Device Infections in the United States: 1996 through 2003

Abstract: To the Editor: Clinical indications for cardiac rhythm management devices (CRMDs) have expanded dramatically. The impact of this expansion upon rates of CRMD infection, a complication of device therapy that often requires system explantation (1), has not been clearly defined.We hypothesized that the current growth in implantable cardioverter defibrillator (ICD) utilization would impact rates of CRMD infection, both by expanding and changing the demographics of the population at risk. We analyzed a nationally r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
251
4
3

Year Published

2010
2010
2016
2016

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 350 publications
(265 citation statements)
references
References 6 publications
7
251
4
3
Order By: Relevance
“…Along with the increase in device implantation, the incidence of device infections has also been increasing, but at a faster rate. (Voight et al, 2006). In the USA, data from Medicare recipients from 1990 to 1999 showed an increase in the number of device infections from 0.94 per 1000 recipients to 2.11 per 1000 recipients, an increase of 124%; the estimated rate of infection of endocardial leads being between 1 and 2%, but varying from 0.13 to 12.6%.…”
Section: Complications Of Pacemaker Implantation 273mentioning
confidence: 99%
See 1 more Smart Citation
“…Along with the increase in device implantation, the incidence of device infections has also been increasing, but at a faster rate. (Voight et al, 2006). In the USA, data from Medicare recipients from 1990 to 1999 showed an increase in the number of device infections from 0.94 per 1000 recipients to 2.11 per 1000 recipients, an increase of 124%; the estimated rate of infection of endocardial leads being between 1 and 2%, but varying from 0.13 to 12.6%.…”
Section: Complications Of Pacemaker Implantation 273mentioning
confidence: 99%
“…In the USA, data from Medicare recipients from 1990 to 1999 showed an increase in the number of device infections from 0.94 per 1000 recipients to 2.11 per 1000 recipients, an increase of 124%; the estimated rate of infection of endocardial leads being between 1 and 2%, but varying from 0.13 to 12.6%. (Cabell et al, 2004;Voight et al, 2006). Grimm et al (1993) reported an incidence of ICD system infection ranging from 2 to 8%.…”
Section: Complications Of Pacemaker Implantation 273mentioning
confidence: 99%
“…While comparing infections of cardiac devices to total joint replacements following dental procedures may be inappropriate, it may serve as a good area of investigation for the AAOS going forward in making potentially improved recommendations regarding prophylaxis. 35 Patients receiving CIEDs tend to be older and suffer from more comorbidities than the population as a whole. 36 The increased prevalence of CIEDs, coupled with their presence in older, sicker patients, has led to an increased incidence of CIED infection.…”
Section: Dental Proceduresmentioning
confidence: 99%
“…33,34 Notably, the number of hospitalizations resulting from CIED infections increased 3.1-fold between 1996 and 2003, significantly outstripping the increase in CIED prevalence. 35 Endocarditis and device-related infections are the most common types of infections complicating CIED placement. 33,34 Between 60% to 80% of these infections are caused by Staphylococcus species; 42% are caused by coagulase-negative Staphylococcus alone.…”
Section: Dental Proceduresmentioning
confidence: 99%
See 1 more Smart Citation